Analytical model for prediction of temperature distribution in early age mass concrete - Donald Chidiebere, Ugwuanyi; Fidelis Onyebuchi, Okafor (International Journal of Engineering and Technology, 2020)
Thermally induced cracks have far-reaching implications on the durability of concrete structures. When cement mixes with water, the reaction is exothermic implying the release of heat. In the case of mass concrete structures, quite a substantial increase in internal temperature may be experienced depending on the ambient temperature and cement content in the mix. The objective of the paper is to develop a mathematical model to predict the time dependent temperature profile in early age mass concrete. Mass concrete block was used to verify the model. Type-K thermocouples placed at various positions and digital thermometer was used to monitor the temperature distribution within the mass concrete block at intervals. The highest temperature values occurred within the core of the mass concrete after one day of concrete placement. Analytical model was developed by applying method of separation of variables and orthogonality relation to two dimensional unsteady state heat conduction equations. The model equation was evaluated and using MATLAB based computer programe. The model successfully predicted the temperature variation within the mass concrete with time. It is therefore suitable for use in the assessment of thermal cracks potential in mass concrete structures.Â